A paratubal cyst associated with flegmonous appendicitis: a case report and review of literature. Issue 2 (April 2017) - Erikci, Volkan S.; Payza, Demet; Ergin, Malik; Hoşgör, Münevver
Abstract : Paratubal cysts (PTCs) are rare clinical entities and are believed to originate from the mesothelium or to be a remnant of Mullerian duct and Wolffian duct. These masses have been reported in all age groups, beginning from the premenarchial period up to menopause, and are mostly benign. A 14-year-old girl with flegmonous appendicitis diagnosed and treated during the management of PTC is presented. This report shows that PTC and flegmonous appendicitis can be seen together as distinct entities in children.